Effects of selected herbicides on activity of Stenotrophomonas maltophilia and growth of aerobic rice, and their persistence in soil - Nahi, Armita (2015)
Aerobic rice cultivation has come up as a promising alternative for flood-irrigated rice system in terms of water use recently. Bio-fertilizer, consisting of beneficial N2 fixing bacteria can promote crop production and nutrient uptake efficiency. Herbicides, the most succesfull chemical weed management approach in direct seeded rice may cause hazardous effects on plant and soil microbes when they come into contact. This study was conducted in laboratory and glasshouse conditions with the following objectives; (i) to determine the effects of three selected rice herbicides on growth and N2 fixing activity of diazotrophic Stenotrophomonas maltophilia (Sb16) (ii) to determine the effects of Sb16 bacterial inoculation and application of three selected rice herbicides on growth of aerobic rice and the soil microbial and chemical properties (iii) to determine the effect of Sb16 on persistence of three selected rice herbicides in soil. The effects of paraquat, pretilachlor and 2, 4-D on growth and N2 fixing activity of Sb16 and pH of Jensen N-free medium were determined in-vitro at every 24-h interval within 7 days of incubation period. The effects of Sb16 bacterial inoculation and application of paraquat, pretilachlor and 2, 4-D on growth of aerobic rice, soil microbial population and chemical properties and their persistence in sterilized and non-sterilized soil were determined under glasshouse condition. Results from in-vitro experiment showed the significant (P≤0.05) decrease of growth of Sb16 by 7.29 and 7.22 log10 cfu.mL-1 in samples amended with full and double doses of herbicides compared to control and half dose (7.37 log10 cfu.mL-1). N2 fixing activity of Sb16 significantly (P≤0.05) increased by 1.66 Nmol C2H4/mL/h with half dose of 2, 4-D compared to control (0.58 Nmol C2H4/mL/h). The growth parameters of aerobic rice, population of total bacteria and diazotrophs and soil chemical properties showed higher values in inoculated samples treated with herbicides compared to non-inoculated samples. The longest half lives of paraquat in sterilized and non-sterilized soil were recorded by 866.38 and 198.3 days in non-inoculated samples treated with double dose. Half lives of 58.74 and 99.01 days were obtained in inoculated and non-inoculated sterilized soil samples, respectively treated with double dose of pretilachlor. Sb16 is recommended as a beneficial biofertilizer in aerobic rice cultivation. Sb16 can promote the aerobic rice production and nutrient uptake in soil applied with paraquat, pretilachlor and 2, 4-D at their recommended dose. Sb16 might be useful in decontamination of aerobic rice field soil applied with pretilachlor and 2, 4-D at their recommended dose under natural soil conditions.